The Role of Combination Therapies in Optimizing Diabetes Management - Amin, Rabia; Ali, Yasir; Idrees, Sana; Ashraf, Ahmad Bilal; Safeer, Bushra; Manzoor, Adnan (Indus Journal of Bioscience Research, 2024)
Objective: To evaluate the efficacy of combination therapies in optimizing diabetes management among patients with type 2 diabetes (T2D) in Pakistan, focusing on glycemic control and treatment adherence. Methodology: A prospective, observational study was conducted at the Department of Medicine, Jinnah Hospital, Lahore from March 2023 to March 2024. A total of 250 patients were randomly assigned to either the intervention group (combination therapy) or the control group (standard therapy). Glycaemic control was assessed using HbA1c levels, while adherence was measured using the Diabetes Self-Management Questionnaire (DSMQ). Statistical analyses, including t-tests, were performed with a significance level set at (p < 0.05). Results: The intervention group showed significantly lower HbA1c levels (mean ± SD: 6.7 ± 1.0%) compared to the control group (8.1 ± 0.9%; (p < 0.0001\)). Adherence scores were higher in the intervention group (87 ± 8%) than in the control group (72 ± 10%; (p < 0.0001\)). The intervention group also had better weight control (72.5 ± 10.2 kg vs. 78.3 ± 12.1 kg; \(p < 0.05\)) and maintained better blood pressure profiles. These findings demonstrate the superior efficacy of combination therapies in achieving improved glycemic outcomes and adherence. Conclusion: Combination therapies offer significant advantages in managing T2D in Pakistan, improving glycemic control and adherence. The study underscores the need for broader adoption of combination therapies and further research on their cost-effectiveness and long-term outcomes.